Fibulin-5: two for the price of one maintaining pelvic support - Gina M. Northington (The Journal of Clinical Investigation, 2011)
Pelvic organ prolapse (POP) is a disabling disorder in women characterized by a loss of pelvic floor support leading to the herniation of the uterus into or through the vagina. POP is a complex problem that likely involves multiple mechanisms, and available therapies are limited. In this issue of the JCI, Budatha et al. explore the dual role carried out by fibulin-5 in facilitating the assembly of normal elastic fibers and inhibiting MMP-9 activity, revealing a new mechanism critical to the maintenance of pelvic organ support.